Long Term Solutions to Cross-border Disaster Displacement: Lessons from West Africa (African Human Mobility Review, 2021)
West Africa is known across the world for its admirable adherence to its longheld principles of hospitality and inclusion. It is also a sub-region whosepopulation shares a deep common history, a fact that is ever more evident in theon-going integration of the politics and communities of this highly mobile area.States in the region have advanced measures for disaster risk management andresponse, and are forward looking in terms of the implications of climate change.Many relocation projects have already been developed and implemented in someWest African countries, generally within national borders, in response toenvironmental disasters (e.g. contamination of the Niger River) or for economicreasons (e.g. villages relocated in western Ghana to make way for miningcompanies). Although fewer examples exist, some relocation projects specificallyconcern persons vulnerable to the adverse effects of climate change.